REDUCTION OF GAS PORES AND NONMETALLIC IMPLEMENTS IN CASTINGS FROM 35XГСЛ AND 110Г13Л STEEL (Web of Technology: Multidimensional Research Journal, 2024)
A technology has been developed for producing high – quality foundry products with high physical and mechanical properties without non – metallic and gaseous pores by treating steel grades 35ХГСЛ and 110Г13Л with oxidizing elements in and outside the furnace.